SPEAKING PERFORMANCE AND PROBLEMS FACED BY ENGLISH MAJOR STUDENTS AT A UNIVERSITY IN SOUTH SUMATERA - Hariswan Putera Jaya; Ismail Petrus; Nova Lingga Pitaloka (University of Kuningan, 2022)
The objectives of this study were to discover the students’ speaking performance, speaking problems, and factors associated with the problems. The participants were the university students of an English education program in South Sumatera. To collect the data, speaking performance test, questionnaire, and open-ended questions were used. The findings showed that 42% of the participants did well and 58% did not perform well in the speaking test. The speaking problems were categorized as affected-related problems (self-confidence and anxiety), socially related problems (difficulties to find opportunities to learn English and comprehension in speaking class), and linguistically related problems (fluency, grammar, vocabulary, and pronunciation). The factors causing the speaking problems are lack of general knowledge, lack of speaking practice, fear of mistake, lack of words usage and grammar practice, low motivation, low participation, reading laziness, shyness, less dictionary usage, nervousness, fear of criticism, and unfamiliar words pronunciation. The data were calculated using Chi-Square Association with p-value (603.508) which is greater than the critical value (70.003). Therefore, there is a significant association between the speaking problems and the factors causing the problems.Keywords: causes of problems; speaking performance; speaking problems